2022
DOI: 10.1186/s40795-022-00630-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal autonomy but not social support is a predictor of child feeding indicators in the Northern Region, Ghana

Abstract: Background Child malnutrition may be mediated by poor infant and young child feeding (IYCF) practices. This study sought to explore if maternal social support or autonomy was related to IYCF indicators in Northern Region, Ghana. Methods An analytical cross-sectional study was conducted with 395 randomly sampled mother–child pairs from 8 health facilities. Data were collected on socio-demographic characteristics, social support and autonomy statuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…As a main finding, it was found that women with a lower level of autonomy had a higher probability of having a child with anemia, which coincides with the results of studies carried out in Africa and Asia [22,51]. In contrast, evidence shows that women with a higher level of autonomy and financial stability tend to invest more in household nutrition, which translates into improved nutritional status and growth in children [16,[35][36][37]. In addition, it has been observed that the dimension of autonomy in health-related decisions is a key factor in obtaining positive nutritional outcomes in children [16,36].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As a main finding, it was found that women with a lower level of autonomy had a higher probability of having a child with anemia, which coincides with the results of studies carried out in Africa and Asia [22,51]. In contrast, evidence shows that women with a higher level of autonomy and financial stability tend to invest more in household nutrition, which translates into improved nutritional status and growth in children [16,[35][36][37]. In addition, it has been observed that the dimension of autonomy in health-related decisions is a key factor in obtaining positive nutritional outcomes in children [16,36].…”
Section: Discussionsupporting
confidence: 77%
“…The inclusion of covariables was made on the basis of previous studies that had evaluated the association of interest [16,[35][36][37]. Thus, the following variables were included: age of child (6-23, 24-35, 36-59), sex of child (male, female), age of mother (15-24, 25-34, 35-49), ethnicity (native, non-native), marital status (married, cohabiting), health insurance (yes, no), number of children (0, 1-3, 4-7), number of people in the household (0-4, 5 or more), area of residence (urban, rural), wealth quintile (poorest [Q1], poorer, middle, richer, richest [Q5]), natural region (Coast, Highlands, Jungle).…”
Section: Covariablesmentioning
confidence: 99%